Cortical Bone Stem Cell Therapy Preserves Cardiac Structure and Function After Myocardial Infarction. Issue 11 (10th November 2017) - Sharp, Thomas E.; Schena, Giana J.; Hobby, Alexander R.; Starosta, Timothy; Berretta, Remus M.; Wallner, Markus; Borghetti, Giulia; Gross, Polina; Yu, Daohai; Johnson, Jaslyn; Feldsott, Eric; Trappanese, Danielle M.; et al.
Abstract : Rationale: : Cortical bone stem cells (CBSCs) have been shown to reduce ventricular remodeling and improve cardiac function in a murine myocardial infarction (MI) model. These effects were superior to other stem cell types that have been used in recent early-stage clinical trials. However, CBSC efficacy has not been tested in a preclinical large animal model using approaches that could be applied to patients. Objective: : To determine whether post-MI transendocardial injection of allogeneic CBSCs reduces pathological structural and functional remodeling and prevents the development of heart failure in a swine MI model. Methods and Results: : Female Göttingen swine underwent left anterior descending coronary artery occlusion, followed by reperfusion (ischemia–reperfusion MI). Animals received, in a randomized, blinded manner, 1:1 ratio, CBSCs (n=9; 2×10 7 cells total) or placebo (vehicle; n=9) through NOGA-guided transendocardial injections. 5–ethynyl–2′deoxyuridine (EdU)—a thymidine analog—containing minipumps were inserted at the time of MI induction. At 72 hours (n=8), initial injury and cell retention were assessed. At 3 months post-MI, cardiac structure and function were evaluated by serial echocardiography and terminal invasive hemodynamics. CBSCs were present in the MI border zone and proliferating at 72 hours post-MI but had no effect on initial cardiac injury or structure. At 3 months, CBSC-treated hearts had significantly reduced scar size, smaller myocytes, and increased myocyte nuclear density. Noninvasive echocardiographic measurements showed that left ventricular volumes and ejection fraction were significantly more preserved in CBSC-treated hearts, and invasive hemodynamic measurements documented improved cardiac structure and functional reserve. The number of EdU + cardiac myocytes was increased in CBSC- versus vehicle- treated animals. Conclusions: : CBSC administration into the MI border zone reduces pathological cardiac structural and functional remodeling and improves left ventricular functional reserve. These effects reduce those processes that can lead to heart failure with reduced ejection fraction. Abstract : Supplemental Digital Content is available in the text.